The Cytosolic Tail Dipeptide Ile-Met of the Pea Receptor BP80 Is Required for Recycling from the Prevacuole and for Endocytosis - Saint-Jean, B.; Seveno-Carpentier, E.; Alcon, C.; Neuhaus, Jean-Marc; Paris, Nadine (My University, 2010)
Pea (Pisum sativum) BP80 is a vacuolar sorting receptor for soluble proteins and has a cytosolic domain essential for its intracellular trafficking between the trans-Golgi network and the prevacuole. Based on mammalian knowledge, we introduced point mutations in the cytosolic region of the receptor and produced chimeras of green fluorescent protein fused to the transmembrane domain of pea BP80 along with the modified cytosolic tails. By analyzing the subcellular location of these chimera, we found that mutating Glu-604, Asp-616, or Glu-620 had mild effects, whereas mutating the Tyr motif partially redistributed the chimera to the plasma membrane. Replacing both Ile-608 and Met-609 by Ala (IMAA) led to a massive redistribution of fluorescence to the vacuole, indicating that recycling is impaired. When the chimera uses the alternative route, the IMAA mutation led to a massive accumulation at the plasma membrane. Using Arabidopsis thaliana plants expressing a fluorescent reporter with the full-length sequence of At VSR4, we demonstrated that the receptor undergoes brefeldin A-sensitive endocytosis. We conclude that the receptors use two pathways, one leading directly to the lytic vacuole and the other going via the plasma membrane, and that the Ileu-608 Met-609 motif has a role in the retrieval step in both pathways.